The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fimmu.2022.882407
|View full text |Cite|
|
Sign up to set email alerts
|

The cGAS-STING Pathway Affects Vertebral Bone but Does Not Promote Intervertebral Disc Cell Senescence or Degeneration

Abstract: The DNA-sensing cGAS-STING pathway promotes the senescence-associated secretory phenotype (SASP) and mediates type-I interferon inflammatory responses to foreign viral and bacterial DNA as well as self-DNA. Studies of the intervertebral disc in humans and mice demonstrate associations between aging, increased cell senescence, and disc degeneration. Herein we assessed the role of STING in SASP promotion in STING gain- (N153S) and loss-of-function mouse models. N153S mice evidenced elevated circulating levels of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
(100 reference statements)
0
12
0
Order By: Relevance
“…A 0.4 N compressive preload was applied, followed by a monotonic displacement ramp at 0.1 mm/s until failure. Force-displacement data were digitally captured at 25 Hz and converted to stress-strain using a custom GNU Octave script with µCT-based geometric measurements, as previously described(55, 56).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 0.4 N compressive preload was applied, followed by a monotonic displacement ramp at 0.1 mm/s until failure. Force-displacement data were digitally captured at 25 Hz and converted to stress-strain using a custom GNU Octave script with µCT-based geometric measurements, as previously described(55, 56).…”
Section: Methodsmentioning
confidence: 99%
“…Following Safranin-O/Fast Green/Hematoxylin staining, images were acquired on a light microscope (Axio Imager 2; Carl Zeiss Microscopy) using 5x/0.15 N-Achroplan (Carl Zeiss) objective and Zen2™ software (Carl Zeiss). The health of disc compartments was assessed by at least four blinded graders using Modified Thompson Grading(56, 5861). Picrosirius red staining (Polysciences, 24901) was performed to assess collagen fibril thickness, and images were acquired using 4x/0.25 Pol /WD 7.0 (Nikon) objective on a polarizing light microscope (Eclipse LV100 POL; Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…STING promoted senescence and apoptosis in IVD via the IRF3 pathway, which can be a therapeutic target as suggested by in vivo and in vitro studies [ 46 ]. However, a recent study using N153S mice (with constitutively active STING) and STING −/− mice reported that the cGAS-STING pathway is not involved in the regulation of IVD senescence and degeneration [ 183 ]. Report showed that constitutive STING activity or the absence of STING in mice has no evidence of accelerated disc senescence or disc degeneration, rather the cGAS-STING pathway was involved in the maintenance of trabecular bone in the vertebrae [ 183 ].…”
Section: Therapeuticsmentioning
confidence: 99%
“…However, a recent study using N153S mice (with constitutively active STING) and STING −/− mice reported that the cGAS-STING pathway is not involved in the regulation of IVD senescence and degeneration [ 183 ]. Report showed that constitutive STING activity or the absence of STING in mice has no evidence of accelerated disc senescence or disc degeneration, rather the cGAS-STING pathway was involved in the maintenance of trabecular bone in the vertebrae [ 183 ]. It was noted that systemic hypercytokinemia was associated with cGAS-STING activation [ 183 ].…”
Section: Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation